Lokomotywa na nowych torach, czyli jak uwspółcześnia się Tuwima - Janusz-Lorkowska, Monika (Załącznik Kulturoznawczy, 2019)
The aim of this paper is an attempt to understand the provenance of various contemporary adaptations and interpretations of the poem Locomotive by Julian Tuwim. Selected and discussed examples of literary works based on Tuwim’s Locomotive deviate so much from the original that they are considered not in terms of adaptation or intersemiotic translation, but as inspiration, artistic creation and reinterpretation. One of the reasons for this approach to Tuwim’s legacy is the use of right to quote for artistic purposes guaranteed by Polish copyright law, which makes it possible to refer to someone’s work without an obligation to ask for authors’ or their inheritors’ permission. The article also briefly recalls the history of the poem Locomotive and basic interpretations of its original form.